Review on Exergy and Energy Analysis of Solar Air Heater - Ahmad Fudholi; Kamaruzzaman Sopian (Institute of Advanced Engineering and Science, 2018)
Solar air heater (SAH), which is the most essential component of solar drying systems, receive solar energy and convert it into thermal energy. This review presents descriptions and previous works conducted on performances analysis of SAHs. Exergoenviroeconomic, exergoenvironmental, environmental, and exergy analyses are also presented. In addition, results on the performances of SAHs are summarized. The exergy and energy efficiencies of SAHs at laboratorium testing range from 8% to 61% and from 30% to 79%, respectively.